Bit-error rate (BER) performance of rotated QAM signals over fading channels - Chiu, Amos Wei Hao (Nanyang Technological University, 2020)
The Quadrature Amplitude Modulation (QAM) Scheme is a digital modulation scheme that is implemented through the use of In-Phase and Quadrature modulation to provide both amplitude and phase modulation. A variation of the QAM scheme is the Rotated QAM scheme where the entire QAM constellation is rotated about the In-Phase and Quadrature origin by a given angle. This project aims to investigate the Bit Error Rate (BER) performance of Rotated QAM scheme under fading channels. In this project, to evaluate the performance of the QAM schemes, the Bit Error Rate (BER) results of Conventional QAM and Rotated QAM schemes are simulated under certain fading channel conditions using MATLAB. This study will include the simulation of flat Rayleigh and Rician fading channels with the inclusion of Additive White Gaussian Noise (AWGN) as well as the simulation for an OFDM channel under flat Rayleigh fading. The simulations will be done over a range of signal-to-noise ratios and it will also include different QAM modulation levels as well as a range of rotation angles for the rotated QAM scheme. The simulation results for both rotated and conventional QAM schemes will be compared with each other to determine the difference in the BER performance.